MECHANISMS AND CLINICAL PERSPECTIVES OF ALLERGEN-SPECIFIC IMMUNOTHERAPY - Akhvlediani , Leila; Izmailovich, Marina; Gazaliyeva , Meruyert; Skvortsova , Anna; Tanriverdiev , Kanan (Interdisciplinary Approaches to Medicine, 2024)
Introduction: Allergic rhinitis (AR) is a prevalent condition in Kazakhstan, characterized by high sensitization to weed pollens, particularly Artemisia, with sensitization levels significantly exceeding those observed in Europe. AR often leads to complications such as bronchial asthma (BA) and other respiratory conditions. The "unified airways" concept emphasizes the interconnected nature of upper and lower airway inflammation, with ASIT showing promise in mitigating these effects. Materials and Methods: A systematic review included 51 articles published between 2013 and 2024, selected from databases such as PubMed and Scopus. Studies focused on ASIT in AR and the role of vitamin D. Inclusion criteria required full-text original research and systematic reviews in Russian and English, specifically addressing allergen-specific immunotherapy. Results and Discussion: ASIT promotes immunological tolerance through mechanisms such as suppression of Th2 activity, increased IgG4 production, and reduced effector cell activation. Vitamin D, particularly 25(OH)D, plays a pivotal immunomodulatory role, supporting Treg and Breg cell function, and mitigating allergic inflammation. Clinical trials demonstrate that vitamin D supplementation enhances ASIT outcomes, especially in pediatric patients. Conclusion: Integrating cholecalciferol into ASIT protocols enhances efficacy and safety by addressing vitamin D deficiency, a factor linked to more severe allergic diseases. This highlights the importance of personalized treatment strategies combining ASIT with vitamin D supplementation for optimal outcomes.